Continuing education for forensic medical analysis of the constitutional appeals in Costa Rica - Flores Sandí, Grettchen (2023)
Introduction: Judicially demanding the right to health involves different elements and can lead to changes in continuing education programs. The current trend is to follow this pathway to access low-frequency and high-cost medications. In addition, the Constitutional Court of Costa Rica requests a technical concept from forensic doctors. Objective: To raise the need for continuous updating in specific theoretical-practical academic knowledge required by forensic doctors to guarantee the right to health services. Reflection: The training of forensic medical doctors is focused on evidence and encourages continuous education. Nevertheless, a commitment is necessary in continuing medical education programs such as literature search strategies, critical assessment of evidence, and academic practices that incorporate particular circumstances comparing them with scientific studies. These programs must take into account prevalent medications and pathologies as well as technical-scientific factors that differ in each service provider. Conclusion: A continuing education program about the interpretation and assessment of scientific evidence for proper decision making on health issues would allow medical doctors to judge existing health problems and choose a medication that is the most beneficial for a patient.